Factors associated with occupational asthma among food industry workers: A systematic review - Md Zamri, Ahmed Syahmi Syafiq (Public Library of Science, 2023)
Occupational asthma (OA) is a type of Work-Related Asthma characterised by variable airflow limitation and/or inflammation due to causes and conditions attributable to a particular occupational environment, and not to stimuli encountered outside the workplace. There is an increasing need to extend the depth of knowledge of OA to better manage this condition, especially among food industry workers who are affected by it.